IMMU-08. THE ROLE OF WNT SIGNALING ON T-CELL INFILTRATION IN GLIOBLASTOMA. (5th November 2018) - Tiwary, Shweta; Wei, Jun; Ezhilasaran, Rave; Sulman, Erik; Huang, Suyun; Ferguson, Sherise
Abstract: BACKGROUND: Glioblastomas (GBMs) are considered immunologically cold tumors, making it difficult to apply immunotherapeutic strategies. Oncogenic pathways intrinsic to the tumor or the microenvironment can influence T-cell infiltration. WNT/β catenin is one such pathway implicated in modulating T-cell infiltration in other solid malignancies. In this study, we examine the influence of WNT signaling on the infiltration of T-cells in GBM. METHODS: Using the TCGA dataset, we analyzed the mRNA expression of both β-catenin dependent (canonical) and independent (non-canonical) WNT ligands and CTNNB1 (β-catenin) in GBM. The expressions of these components were correlated with a T-cell signature (CD3e, CD3d, CD3g, CD4, CD8a, and CD8b) and survival. Additionally, multiple GSC cell lines, derived from human GBM samples, were profiled for different WNT ligands and cells with the highest and lowest expression were selected for further experiments. In vitro, we also utilized a T-cell migration assay to measure the effect of WNT ligands (WNT3a and WNT5a) on T-cell migration towards a GL261 monolayer. RESULTS: In silico analysis of the TCGA dataset revealed downregulation of most WNTs in GBM and in 49 evaluated GSC cells lines. In cases with evidence of a T-cell signature, disease-free progression was 2-fold higher than those without evidence of a T-cell infiltration. Additionally, we observed a mutual exclusivity between the T-cell signature and β -catenin expression. WNT5a (non-canonical WNT ligand) had a significantly higher expression in the low-risk group (higher survival *p=1.42e-33) in GBM. Furthermore, in vitro, we observed a 2-fold increase in the migration ability of effector T-cells (CD4+ CD8+) towards the GL261 monolayer in presence of WNT5a. CONCLUSION: This data suggest that the WNT/β-catenin dependent pathway negatively regulates T-cell infiltration whereas the β-catenin independent pathway may have a promoting role.